The Students' Perceptions of Screencast Video Feedback and Their Self-Regulated Learning in Responding to the Feedback - Fatoni, Mohammad; Setiawan, Slamet; Munir, Ahmad; ., Suhartono (KnE Social Sciences, 2024)
Screencast video feedback is relatively new in writing class. Technology development leads the lecturer to provide feedback through the screencast video feedback. The students need screencast video feedback for guidance to write better. The students revise and edit their writing based on the comments given. However, the student’s understanding might differ from the lecturer’s intention. This study investigated students’ perception of screencast video feedback and explored their self-regulated learning in responding to it. It used a qualitative study involving 10 EFL university students using semi-structured interview questions. The data were transcribed and analyzed using thematic analysis of students’ perceptions of the screencast video feedback and their self-regulated learning. The finding showed the students had positive perceptions of the screencast video feedback. In addition, the students constructed self-regulated learning such as setting goals, self-motivating, monitoring, seeking help, adopting, and self-evaluating their writing. This study reveals the benefits to English lecturers to enhance the quality of the feedback in teaching writing. Keywords: screencast video feedback, the students’ perception, self-regulated learning